2016
DOI: 10.1248/bpb.b16-00127
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Parameters of Various Metal Ions and Binding Affinity for Alginate

Abstract: Key words alginate; toxic metal; binding mechanism; affinity Metal ions absorbed via the intestinal tract, respiratory system or skin can cause serious damage to various internal organs, depending on their type and amount. For example, lead (Pb) causes acute damage to the central nervous system, and chronic damage to the kidney and hematopoetic and nervous systems.1,2) Long-term, low-dose exposure to cadmium (Cd) damages the lung (chronic bronchitis, fibrosis, emphysema), kidney (renal tubular degeneration, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…However, our results indicate that it acts predominantly by inhibiting α-glucosidase. We ruled out a substantial contribution of direct binding, because the Km value of Ca-Alg and glucose was 201.6 mM, suggesting only weak binding compared to the binding constants of Alg and metals reported previously 26) . In addition, Ca-Alg did not affect the membrane transport of glucose.…”
Section: Discussionmentioning
confidence: 96%
“…However, our results indicate that it acts predominantly by inhibiting α-glucosidase. We ruled out a substantial contribution of direct binding, because the Km value of Ca-Alg and glucose was 201.6 mM, suggesting only weak binding compared to the binding constants of Alg and metals reported previously 26) . In addition, Ca-Alg did not affect the membrane transport of glucose.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we reported that Ca-Alg reduces absorption and promotes excretion of both strontium (Sr) and cesium (Cs), whereas Na-Alg is effective only for Sr. 20) In addition, we investigated the relationship between the physical parameters of various metal ions and the binding affinity of these metal ions for Alg. 21) Moreover, we found that Ca-Alg suppressed the elevation of blood glucose levels after ingestion of starch in rats and humans by inhibiting the degradation of maltose to glucose by α-glucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that Alg forms a cross-linked structure with divalent or trivalent metal ions, resulting in gel formation. These results might indicate that metal ions with an ionic radius of about 90-120 pm form more robust and water-insoluble gels (Figure 2) [11].…”
Section: Mechanism Of Binding Of Alginate and Metalsmentioning
confidence: 96%
“…Although the effect of Alg on Sr or Cs absorption and excretion has already been reported, there is little information about its effect on other metals. Therefore, we investigated the relationship between the physical parameters of various metal ions, including toxic metal ions, and the binding affinity of these metal ions for Alg [11]. For this purpose, the binding constants (K, mM −1 ) and the binding amount with Alg were evaluated for Sr, Pb, Tb, Dy, Ca, Cd, Mg, Fe(II), Fe(III), Co, Al, Ni, Cs, Cu, Ag, Li, and K. Aqueous solutions of each metal salt and an equivalent amount of Na-Alg were mixed, and the amount of unbound metal remaining in the filtrate was determined using an atomic absorption photometer.…”
Section: Mechanism Of Binding Of Alginate and Metalsmentioning
confidence: 99%
See 1 more Smart Citation